A Systematic Review of the Psychological and Social Consequences of Parental Divorce on Children - Sofiatun, Sofiatun; Deviantony, Fitrio; Kusumawardani, Winda (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2025)
Background: Parental divorce is an increasingly common phenomenon that has the potential to cause psychological problems for children. The family is the bond and initial environment for children to receive guidance, experience, and education as well as values and norms that shape their behavior throughout life. However, in fact not all families have harmonious relationships and choose divorce as a way out to solve problems without thinking about the condition of their children. Aims: This study investigates how parental divorce affects children's psychological well-being. Methods: A Systematic review from 2019 to 2024 of national and international journals from databases, such as PubMed, ResearchGate, ScientDirect, Taylor & Francis, and Google Scholar with the keywords “Divorce”, “Parental Conflict”, “Child Psychology”, “Child Mental Health” was used. Results: The results of the literature review indicate a relationship between parental divorce and child psychology. Children who come from broken home families tend to experience psychosocial disorders, such as depression, low self-esteem, stress, decreased achievement, and so on. Conclusion: Parental divorce has a significant impact on children's psychological development, especially on emotional and mental aspects. Children from divorced families often experience psychological problems. However, there are some studies that mention positive impacts, such as increased independence and resilience in dealing with life.